Sierra Leone - The Road to Recovery : Results from a Beneficiary Impact Assessment - Hackett, Julie (World Bank, Washington, DC, 2012)
This note explores how a community-driven approach has successfully made inroads in Sierra Leone, a country racked by internal violence and without a tradition of widespread civic participation. By mobilizing village members to work together to rebuild physical infrastructure destroyed by the war, the World Bank's National Social Action Project is also rebuilding trust and collective action amongst a divided population. In particular, the project targeted areas not previously serviced by Government, 'newly accessible areas,' (those which were under rebel control until the end of the war in 2002); as well as the most vulnerable population groups within those areas.